The immunibiochemical effect of synobiotic and phytobiotic in vaccinated and unvaccinated chicken - Kamel O. I., marwa; A. A. El-Komy, Ashraf; A. A. Farag, Enas (International Journal of Pharmacology and Toxicology, 2021)
The current study was conducted to evaluate the effects of dietary supplementation of synbiotics, phytobiotics and their mixture on some blood parameters with respct to kidney and liver functions and some histological criteria of broilers. A total of 200 broiler chicks were randomly chosen and divided into eight groups (25 bird in each). The first four groups were unvaccinated chicken and allotted to four dietary treatments, either fed a basal diet (group 1) or the same diet supplemented with 1g synbiotic /kg body weight ( group 2) , 1g phytobiotic /kg body weight (group 3) and 1g synbiotic plus 1g phytobiotic/kg body weight (group 4) .The same previous treatments were received by four vaccinated chicken groups 5, 6,7 and 8 , respectively. Synobotic and phytobiotic tended to increase AST and ALT levels in vaccinated chicken during different periods. The mixture synbiotic and phytobiotic led to no significant increase in AST with unvac-cinated and increase of ALT level in vaccinated groups. Also, previous feed additive increased total protein in both vaccinated and unvac-cinated chickens. Supplementation mixture of both synbiotic and phytobiotic to diet increased total protein in unvaccinated and vaccinated chicken. Rations supplemented with synobiotic and phytobiotic increased albumin level in unvaccinated chicken and decreased with vac-cinated chicken during different periods. Consequently, mixtures of synobiotic and phytobiotic appeared the same trend. On the other, using synobiotic and phytobiotic showed increase globulin level with unvaccinated chicken and decrease with vaccinated chicken, while the mixture of them gave higher level of globulin with unvaccinated or vaccinated chicken during different periods, except at 21 day, the globulin level had slight decrease with unvaccinated chicken. At the same time supplementation synobiotic and phytobiotic or their mixture with unvaccinated or vaccinated chicken revealed normal histological criteria. In conclusion, dietary supplementation of syonbiotic and phytobiotic improved the gut health by decreasing the caecal total coliform count with no adverse effect. The aim of this experiment is to study the effect of dietary supplementation of synobiotic, phytobiotic and their mixture on kidney and liver functions and some histological criteria of broiler chicken.